Black Slavery and Racialization Processes in the Iberian Colonial Atlantic: Conflicting Perspectives - Jiménez González, Aitor (EUNOMÍA. Revista en Cultura de la Legalidad, 2019)
Racism, as a hierarchizing and ordering ideology of the social reality arose as a part of the legal order. Norms and rules were its constituent body. Territories submitted to colonial governance of European nations were its experimentations camps. Despite of the importance of racialized legal orders in colonial Latin-America, the region lacks of its own coherent body of socio-legal studies looking at the colonial racial relations. In this paper I will scrutinize relevant contributions in Law and Race looking at racial relations in colonial Latin America, specifically those related with black slavery. I aim to expose the substantial difference between Latin-American and Anglo-Saxon perspectives. My intention with that is to remark the necessity of developing a non anglocentered analytical perspective of the Iberian colonial world. This will give academics the possibility, not only of understanding Latin-American racial history but also of apprehending the nature of the current racialization processes.